BANK RISK AND MARKET DISCIPLINE - Taswan, Taswan; Tandelilin, Eduardus; Husnan, Suad; Hanafi, Mamduh M. (Journal of Indonesian Economy and Business, 2012)
This paper investigates the issue of bank risk taking. Specifically we investigate two main issues: (1) determinants of bank risk, and (2) market discipline to the banks either in implicit, explicit guarantee systems, and all periods. Using Indonesian data, we find that domestic, foreign, and ownership concentration have positive impact on bank risk. Bank shareholders engage in entrenchment behaviour, rather than convergence behaviour. We further find that charter value and compliance to regulation have negative impact on bank risk. Next, we find that market disciplines the banks. Market disciplines the banks at thesame degree in implicit and explicit deposit guarantee systems. Our findings highlight the importance of paying close attention to banks ownership, charter value, and compliance to regulation. Furthermore, since we find that market disciplines the Banks at the same degree in explicit and implicit guarantee systems, we need to investigate this issue further.This finding highlights research potential in the future: to investigate disciplining behaviour from various types of depositors.Keywords: bank ownership, market discipline, risk, entrenchment, convergence, and deposit insurance